Design of High Gain and Improved Front-to-Back Ratio Multilayer Microstrip Patch Antenna using Modified Feed Line - Partha Kumar Deb; Tamasi Moyra; Bidyut Kumar Bhattacharyya (ASEAN Journal on Science and Technology for Development, 2022)
A novel high gain miniaturized rectangular microstrip patch antenna is proposed with a high front-to-back ratio (FBR) using a modified feed line and two single-sided substrate layers to operate at 2.4 GHz frequency. The feed line is modified using a step impedance technique to achieve resonance at the operating frequency. The matched impedance of the feed line helps achieve enhanced bandwidth and antenna miniaturization. The substrate layers are introduced to achieve an enhanced gain and FBR of 6.329 dBi and 27.64 dB, respectively. The impedance bandwidths of 106.9 and 94.1 MHz are achieved for the two separate designs. These proposed designs have a total circuit area occupancy of 0.4 ?0 × 0.304 ?0. The antenna has been designed and fabricated using FR4 substrate material. The measured results are in good agreement with the simulated results.